GENDER DIFFERENCES IN EMOTION FRAMING - Zardiashvili, Natia (Online Journal of Humanities ETAGTSU, 2020)
Expressing and understanding emotions can be considered one of the key activities of our lives. However, at times, the feelings of a person might be misinterpreted or the initial emotional response in a partner might be misunderstood. There have been various studies concerning the differences in emotion expression between male and female target groups (Chaplin 2015). This research discusses the issues of emotion framing in public discourse paying particular attention to the ways male and female speakers frame emotions and influence the audience. Consequently, the article focuses on emotion framing and compares two presidential candidacy speeches (Hilary Clinton’s and Donald Trump’s) from the USA elections recorded in June 2015. The research showed that both speakers follow the same pattern of emotion framing (positive social identity construction-framing-emotion implication) but used different techniques and emphasise different values throughout the speech. These differences were linked to Hofstede’s (1983) definition of cultures with high versus low masculinity rate and finally, assumptions were made about how gendered stereotypes influence different ways of framing emotions. Full Text (PDF)